Predicting College Students’ Bike-Sharing Intentions Based on the Theory of Planned Behavior - Chen, Xiaofang (Frontiers in Psychology, 2022)
Shared bicycles are sustainable and effective transportation tools in college campuses. Accordingly, this study aimed to assess the behavioral intention of college students toward bike-sharing as an environmentally friendly and social mode of travel. It applied the Theory of Planned Behavior (TPB) framework to a bike-sharing context and explored the impact of perceived benefits and government policy on college students’ bike-sharing usage. A survey of 934 college students was conducted in Zhejiang province to test the proposed model, and 782 were valid. The findings pointed out that attitude, subjective norms, and perceived behavioral control have a significant and positive impact on college students’ intentions toward bike-sharing. Meanwhile, the empirical results revealed that perceived benefits and government policy were the important factors driving college students’ intention and behavior for bike-sharing usage. Moreover, the results ascertained that the intention was aligned with actual actions; eventually, some targeted managerial implications are presented. This study enhances the current understanding of the usage behavior of college students in bike-sharing and provides timely insights for government policymakers and enterprise operators to promote sustainable bike-sharing practices in China and other countries.